Evolution of smart grid assessment methods: science mapping and performance analysis - Zarate Perez, Eliseo Juan (2021)
ABSTRACT The field of research related to smart grid (SG) assessment methods is broad and fragmented owing to the contribution of the various disciplines and approaches involved. This presents difficulties in obtaining useful and unbiased information for future studies. Hence, a full review of the contributions could provide a comprehensive critical perspective. In this article, SciMAT software is used to determine the evolution of this research field through a systematic review of the literature based on 331 original research articles. In addition, hidden issues and their development in this field have been identified for the period 2009–2020 to produce strategic diagrams of the thematic evolution and performance indicators of the research field. The results show that SG assessment methods are important topics, and the research field demonstrates an evolutionary trend that has not yet reached a maturity stage in each of the SG-related research topics. The most important topics, such as electric power transmission networks and environmental impact, are highlighted, with a particular interest in the transmission of electric power, application of photovoltaic systems, and life cycle analysis.